Penerapan Metode Regresi Linear dalam Analisis Statistik Penggunaan Internet via Telepon Seluler di Indonesia Berdasarkan Data BPS - Amelia Nur Azizah; Vevinciya Dila Dita; Juwita Septiani; Denaya Fadilah; Stella Putriseptiyani Septeragil; Purwadi Purwadi (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
This study aims to apply the linear regression method in analyzing the trend of internet usage via mobile phones across all provinces in Indonesia based on data from the Central Statistics Agency (BPS) for the period 2020–2024. Internet access through mobile phones is the dominant medium in Indonesia, with the national average ranging from 98.25% to 99.11% during the period. This study uses secondary data from BPS covering 34 provinces in Indonesia. The analysis method used is simple linear regression with year as the independent variable (X) and the national average percentage of internet usage via mobile phones as the dependent variable (Y). The analysis produced the regression equation Y = -276.01 + 0.1853X with a coefficient of determination R² = 0.7831, meaning approximately 78.31% of the variation in internet usage growth can be explained by the time factor (year). Based on this regression model, internet usage via mobile phones in Indonesia is predicted to reach 99.27% in 2025. The results indicate a consistent positive trend in mobile internet usage in Indonesia, although provincial variations exist.